Pharmacotherapy and Associated Factors in Women with Gestational Diabetes - Ghodrati, Niloofar; Nouhjah, Sedigheh; Shahbazian, Hajieh; Jahanfar, Shayesteh; Shahbazian, Nahid; Cheraghian, Bahman; Jahanshahi, Alireza (International Pharmacy Acta, 2018)
Introduction Pharmacotherapy is an indicator of severity of hyperglycemia in pregnancy that may reflect β-cell dysfunction in women with gestational diabetes mellitus. Methods and Results Life after gestational diabetes Ahvaz Study (LAGAs) is a population-based prospective cohort study to investigate potential short and long-term metabolic outcomes of gestational diabetes in mothers and their offsprings. Pregnant women attending 25 urban public and private centers seeking prenatal care were recruited from March 2015. 19.3% (34/176) of women with gestational diabetes required pharmacotherapy in pregnancy (12.5% insulin and 6.8% metformin). The mean age of women who needed pharmacotherapy was 31.0 (SD, 4.6) years vs 29.3 (SD, 5.3) years in diet-treated women. Cesarean delivery, higher FPG at first visit of pregnancy and premature delivery were significantly associatiated with need to pharmacotherapy in pregnancy (p<0.05). Conclusions Although the use of oral anti-diabetic drugs in pregnancy is not recommended by the American diabetes Association (ADA), consumption of them in women exposed to gestational diabetes is considerable. Use of insulin or metformin for management of hyperglycemia in pregnancy strongly prognoses metabolic disturbance later in life. Therefore postpartum prevention and screening program for cardiovascular risk factors is important for women with GDM who required pharmacotherapy for management of hyperglycemia in pregnancy.